Recycling Stories: Community Art and Deliberative Democracy Opening Spaces for Civic Engagement - de Oliveira Jayme, Bruno; Germanos, Erika; Saccucci, Brent Franco (Journal of the Canadian Association for Curriculum Studies, 2020)
How can we create meaningful spaces of engagement for citizens who work in the recycling industry in Brazil who suffer marginalization? What can we learn from the Brazilian experience of opening spaces of engagement? Seeking answers for these questions, we entered the journey of participatory action and arts–based research and developed a series of visual arts workshops and public exhibits in the city of São Paulo, Brazil. In this context, the objective of this study is to explore the diverse role of the arts in not just creating spaces for engagement that are inherently deliberatively democratic, but also holding the space for dialogue, knowledge construction and mobilization, and civic engagement.